The social return of investment method as a tool for valuation and impact assessment for libraries - De Leon, Simon V. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Social return on investment (SROI) is an impact assessment framework that measures changes and intangible social values used in both for-profit and non-profit types on institutions. The methods, as espoused by the Social Value International, consists of six procedural stages with seven guiding principles to facilitate discussions and maximize the impact of any activity.